DAMPAK PENGASUHAN OTORITER TERHADAP PERKEMBANGAN SOSIAL ANAK - Lisda Yuni Mardiah; Syahrul Ismet (JCE (Journal of Childhood Education), 2021)
Parenting is fundamental in shaping character. Exemplary attitude of parents is needed for children's development because children do modeling and imitation of the environment. The moral degradation of children, which has recently been found to reflect the poor quality of upbringing from the family. Furthermore, wrong parenting can have an impact on the cause of children's self-concept to be negative, and tend not to be enthusiastic in achieving life goals. This incident can also occur as a result of the authoritarian parenting adopted by the parents. Family is the first environment that influences various aspects of child development, including social development. The conditions and procedures for family life are a conducive environment for children's social life. The purpose of this study was to determine how the effect of authoritarian parenting on children's social abilities. The research method used was literature study by reviewing and analyzing the results of previous research. The results showed that authoritarian parenting has a negative impact on children's social abilities, children with authoritarian parenting tend to close themselves, are not confident and ashamed to face and interact with the social environment